The Determination of Soil Infiltration Rate of Urban Bioretention Design Process in Chiang Mai, Thailand - Sittisom, Prattakorn; Tangsongsuwan, Rapee; Munlikawong, Sikarint; Wongsapai, Wongkot; Sitthikankun, Sitthikorn; Rinchumphu, Damrongsak (Nakhara : Journal of Environmental Design and Planning, 2022)
Stormwater runoff is an issue that is increasingly affecting urban areas because areas that previously were permeable have been developed, and are now impermeable, comprising hard surface areas, whether concrete floors, roads, or buildings. As the size of the problem area increases, the amount of stormwater runoff that needs to be cleared from urban areas increases, and it takes longer for the stormwater to be cleared. The existing basic public drainage systems can no longer sufficiently support the increasing stormwater runoff, directly affecting commuting and lifestyle. These problems have led to the design concept of bioretention, which can be used to increase the efficiency of water infiltration of existing soil areas since a higher water infiltration rate can help relieve the burden on the basic public drainage system and alleviate the abovementioned problems. Bioretention design consists of three layers: the drainage layer at the bottom, the transition layer, and the filter media layer at the top. The critical objective is to design the filter media layer (the top layer) to have a greater infiltration rate than the original soil. This research, therefore, comprises an experiment in which sand is mixed with the original soil to achieve these increased infiltration rates. Three different soil-to-sand ratios were field tested within the area of the Faculty of Engineering, Chiang Mai University, Chiang Mai, Thailand with double-ring infiltrometer technique to test the infiltration rate, 1:1, 1:2, and 1:4. This research also applied Horton's Theory of Perforation Prediction Equations; the experiments demonstrated that adding sand can increase the water infiltration rate. The infiltration rates for soil-to-sand ratios of 1:1, 1:2, and 1:3 are 16.09, 21.53, and 28.90 mm/hr., consecutively. In addition, understanding the relationship between infiltration rate and sand ratio makes it possible to determine the permeation rate as required. Furthermore, knowing the sand ratio is useful for future planning to achieve the appropriate design.